Shared nociceptive dorsal root ganglion neurons participating in acupoint sensitization - Li, Wanrong; Liu, Jia; Chen, Aiwen; Dai, Danqing; Zhao, Tiantian; Liu, Qiong; Song, Jianren; Xiong, Lize; Gao, Xiao-Fei (Frontiers in Molecular Neuroscience, 2022)
When the body is under pathological stress (injury or disease), the status of associated acupoints changes, including decreased pain threshold. Such changes in acupoint from a “silent” to an “active” state are considered “acupoint sensitization”, which has become an important indicator of acupoint selection. However, the mechanism of acupoint sensitization remains unclear. In the present study, by retrograde tracing, morphological, chemogenetic, and behavioral methods, we found there are some dorsal root ganglion (DRG) neurons innervating the ST36 acupoint and ipsilateral hind paw plantar simultaneously. Inhibition of these shared neurons induced analgesia in the complete Freund’s adjuvant (CFA) pain model and obstruction of nociceptive sensation in normal mice, and elevated the mechanical pain threshold of ST36 acupoint in the CFA model. Excitation of shared neurons induced pain and declined the mechanical pain threshold of ST36 acupoint. Furthermore, most of the shared DRG neurons express TRPV1, a marker of nociceptive neurons. These results indicate that the shared nociceptive DRG neurons participate in ST36 acupoint sensitization in CFA-induced chronic pain. This raised a neural mechanism of acupoint sensitization at the level of primary sensory transmission.